Stripping Massage and Literature Review in Post-Thoracoscopic Chest Pain Management - Hsu, Jiun; Yu, Sheng-Pin; Pan, Chien-Te; Huang, Pei-Ming (The Thoracic and Cardiovascular Surgeon, 2023)
The aim of this randomized study was to investigate whether stripping massage (SM) of myofascial trigger points in the lower rhomboid muscle could alleviate chest pain in patients following thoracoscopic surgery. In addition, a literature review was conducted to assess the effectiveness of various pain management techniques. Sixty adult patients who reported a visual analog scale (VAS) score of 4 or higher were randomly assigned to receive conventional analgesics alone (conventional group) or combined with SM twice daily for 2 weeks (SM group). VAS scores and the use of additional analgesics were evaluated on postoperative days 1, 3, 7, 14, and 30. Using the PubMed and Cochrane Library databases, a review of current pain management techniques was carried out up to January 31, 2022. A subgroup analysis was also performed to examine the treatment effect during different surgical periods and techniques. Results showed that the SM group had significantly lower VAS scores on postoperative days 3, 7, 14, and 30 (p < 0.001), as well as a shorter hospitalization duration and reduced need for additional analgesics (p < 0.001). The literature review included a total of 20 studies (2,342 cases of chest pain relief after thoracoscopic surgery), which indicated that serratus anterior plane (SAP) blocks were commonly used as a perioperative approach to reduce pain and opioid consumption. SM and SAP can both serve as adjuvant treatments for chest pain in patients following thoracoscopic surgery, with SM being a safe and noninvasive pain control option after hospital discharge.
Keywords: postoperative pain; surgery; complications; thoracoscopy/VATS